Multi-Track Diplomacy of the Joint State Actor and Non-State Actor Proposed the Maros Pangkep Geopark to Become a UNESCO Global Geopark - Dwi Putro; Tulus Warsito (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2023)
The Maros area has been initiated to be developed into a national geopark in 2015, then to maintain,protect, preserve and be recognized globally. The Maros area is proposed to become a UNESCOGlobal Geopark in 2021. This research aims to understand the process of the government,stakeholders, and the community around the geopark proposed that the Maros Geopark become aUNESCO Global Geopark (UGG). This research used a qualitative method with a descriptivenarrative approach from various sources, articles, websites, and news. The findings from this researchthrough multi-track diplomacy, which focuses on track one (state) and track two (non-state actors),showed that the relevant actors succeeded in turning the Maros Pangkep Geopark into a UGG. Theannouncement was made at a council meeting in Thailand on September 4, 2022, followed by anofficial announcement on May 24, 2023, based on decisions taken at the 216th UNESCO ExecutiveBoard Session in Paris.